2006
DOI: 10.1097/00001813-200606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine plus cisplatin in metastatic breast cancer

Abstract: Our objectives were to assess the efficacy and toxicity of gemcitabine plus cisplatin as first-line therapy in metastatic breast cancer (MBC). Patients with stage IV MBC and no prior chemotherapy for metastatic disease were treated with gemcitabine 1200 mg/m on days 1 and 8, and cisplatin 75 mg/m on day 1 every 21 days. Up to 6 cycles were given. A total of 46 patients with a median age of 49 years (range 24-77) and Karnofsky performance status of 80 or above were enrolled. In total, 238 cycles were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…Overall, the major hematologic toxicities associated with the combination of gemcitabine and cisplatin have been neutropenia and thrombocytopenia, and the major nonhematologic toxicities have been nausea/vomiting, nephrotoxicity and neurotoxicity [26] . While 6.4% of the patients in our trial developed grade 3/4 neutropenia, no thrombocytopenia was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the major hematologic toxicities associated with the combination of gemcitabine and cisplatin have been neutropenia and thrombocytopenia, and the major nonhematologic toxicities have been nausea/vomiting, nephrotoxicity and neurotoxicity [26] . While 6.4% of the patients in our trial developed grade 3/4 neutropenia, no thrombocytopenia was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of gemcitabine and cisplatin was shown to be effective in several trials, inducing response rates between 30 and 52% in patients pretreated with taxanes and/or anthracyclines [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine and cisplatin have demonstrated response rates of 29-62% in previously treated advanced breast cancer patients in the phase II setting; however, a high incidence of thrombocytopenia (up to 32%) was observed necessitating gemcitabine dose reduction [14,22,40]. The two responding breast cancer patients in this study were heavily pre-treated with prior chemotherapy but neither had any prior cisplatin, and the patient with a CR did not receive prior gemcitabine.…”
Section: Discussionmentioning
confidence: 74%